Ignition and combustion behaviour of vegetable oils after injection in a constant volume combustion chamber. (July 2015) - Emberger, Peter; Hebecker, Dietrich; Pickel, Peter; Remmele, Edgar; Thuneke, Klaus
Abstract: The ignition and combustion behaviour of vegetable oils to be used as fuel in combustion engines was researched using a constant volume combustion chamber. The chosen vegetable oils were characterised using the two structure indices average number of carbon atoms AC and average number of double bonds ADB. The structure indices were derived from the composition of the analysed fatty acids. The performance of these two structure indices in estimating differences in fuel properties, such as density, net calorific value, elementary composition and surface tension, was shown. The structure indices were also used to explain ignition and combustion behaviour. Differences in ignition and combustion behaviour were primarily recognised in the ignition delay and the first phase of combustion (premixed combustion). No differences were observed between the vegetable oils in subsequent phases of combustion. The longer the ignition delay, the higher the share was of premixed combustion. Models for the prediction of the ignition delay were developed using ADB. The ignition delay rises with increasing ADB. Differences in AC had no significant impact on the ignition delay. Hence, vegetable oils with a high ignition quality are characterised by a low amount of double bonds. The developed models can be used for estimation of the ignition quality and combustion behaviour of unknown vegetable oils. Highlights: Ten vegetable oils and two vegetable oil mixtures were tested. Two suitable structure indices were developed from the fatty acid composition to predict fuel properties. Differences were detected in the ignition behaviour and in the first combustion phase. Vegetable oils with short ignition delay are characterised by a low number of double bonds.